Immigrants are attracted by local pre‐breeders and recruits in a seabird colony. (14th March 2014) - Szostek, K. Lesley; Schaub, Michael; Becker, Peter H.; Weimerskirch, Henri
Summary Immigration is a major demographic factor shaping population dynamics. However, due to methodological difficulties, the extent of immigration and factors affecting immigration are insufficiently studied. This is also true for seabird colonies. We estimated annual immigration based on a long‐term study of a colony of common terns Sterna hirundo marked with transponders, using a Bayesian integrated population model that links colony size and productivity with individual life histories. Strong annual fluctuations in the number of immigrants were found. To identify whether colony‐specific covariates influenced immigration, we related the number of immigrants to various proxy variables for breeding site quality, specifically colony size, productivity, number of local subadults and local recruits. Numbers of local recruits and local subadults showed strong positive correlations with number of immigrants. We found that variation in immigration rate had strongly contributed to variation in colony growth rate, more so than variation in local recruitment or adult survival. Collectively, results suggest that immigration strongly affects colony growth rate, that the driving force behind immigration is natal dispersal and that immigrants were attracted by local recruits.